The Anamorphosis of Struggle, Confrontation, and Ideological Imagination in Tayeb Salih’s Season of Migration to the North (1966) - Souleymane Diallo (Journal La Sociale, 2021)
The transmedia narrative of the scope of Season of Migration to The North, emphasizes substantial composite creations where specific characters and idiosyncratic plot lines imply a neo-perception method and a post-conception model within the dimensionality of understanding becomes a generative system and a transformative experience. In this run, the anamorphic format of imagination and intellection inside the indigenized process of encoding, designs a new method of normative functionalism, an original attitude of discernments and a prima materia empirical perceptive consignment. Therefore, through a relational value of model and an aesthetic realism, Salih defines an innovative interactive and immersive reality within an analytic functionalism and a psycho-functionalist view in the perspective to transcend the Islamist conservative approach of formal concept analysis and then to deconstruct the Western absorption of temporal concept analysis. It is within this respect, the principle of this paper appears to be a social deconstructionism, a modality and property differentiation concerning the status quo of the Be-ing, and a transformative reform about anthropological prerequisites and requests. In this respect, the realm of functionalism, functional linguistic and aesthetic realism involve this Salih’s object argument in a transgressive object relation.